Association between admission blood sugar levels and length of stay among patients with acute heart failure: A cross-sectional study in Aceh, Indonesia - Naufal Gusti; Teuku Heriansyah; Irwan Saputra (Narra X, 2023)
Heart failure persists to be a major health problem worldwide. Numerous factors associated with this condition have been studied to determine its prognosis. History of diabetes mellitus is one of the factors extensively studied, nonetheless, the correlation between acutely elevated admission blood glucose in critically ill patients or stress hyperglycemia towards the prognosis of heart failure remains inconclusive among previously reported studies. Therefore, the aim of this study was to investigate the correlation between admission blood glucose and the length of stay of acute heart failure patients. A cross-sectional study was conducted in Dr. Zainoel Abidin Hospital, Banda Aceh, Indonesia from July to August 2020. Patients’ data were retrieved from medical records documenting admission blood glucose and length of stay. Total sampling was employed, where eighty-five patients diagnosed as acute heart failure were included. The results showed that patients (n=85) had the general characteristics of being normoglycemic on admission (69.4%) and having 5–10 days length of stay (44.7%) with Killip 2 as the presiding Killip Class (50.6%). According to Gamma’s Correlation Coefficient, the p-value of this study is 0.012 (p< 0.05) with a correlation value of 0.454. Therefore, our study revealed the presence of a significant moderate-correlation between admission blood glucose and the length of stay among patients with acute heart failure.